2009
DOI: 10.1063/1.3055268
|View full text |Cite
|
Sign up to set email alerts
|

Real-time studies of surface roughness development and reticulation mechanism of advanced photoresist materials during plasma processing

Abstract: Surface roughness development of photoresist (PR) films during low pressure plasma etching has been studied using real-time laser light scattering from photoresist materials along with ellipsometric and atomic force microscopy (AFM) characterization. We show that evolution of the intensity of light scattered from a film surface can be used to study the development of surface roughness for a wide range of roughness starting from subnanometer to few hundred nanometers. Laser light scattering in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The characteristic buckling wavelength of 193 nm PR surface roughness resulting from plasma exposure above the T g in the presence of ion bombardment has also been studied 46. This roughness is on the order of micrometers and results in reticulation, a phenomenon that is not encountered in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…The characteristic buckling wavelength of 193 nm PR surface roughness resulting from plasma exposure above the T g in the presence of ion bombardment has also been studied 46. This roughness is on the order of micrometers and results in reticulation, a phenomenon that is not encountered in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…UV-sensitive polymers show increased postplasma etch surface roughness compared to UV-insensitive polymers such as PS. 5,9 From wrinkling theory, a reduced underlayer elastic modulus would increase the magnitude of wrinkling that occurs during formation of the highly stressed, modified layer by ions. We suspect that the observed plasmagenerated UV damage 5,48 in UV-sensitive polymers ͓i.e., 193 nm PR, 5 poly͑␣-methylstyrene͒ 17 ͔ reduces their underlayer modulus and is responsible for the enhanced surface roughness compared to UV-insensitive polymers ͑i.e., 248 nm PR, 5 PS͒ observed under simultaneous ion bombardment and UV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior has been observed in many types of polymers ͓e.g. poly͑methyl methacrylate͒ ͑PMMA͒, 8 193 and 248 nm photoresists 5,6,9,10 ͔ and has been described as a thin, highly crosslinked and graphitized layer. [4][5][6][11][12][13][14][15][16] We have previously shown that under energetic Ar + ion bombardment during plasma etching, a dense, amorphous carbonlike modified layer is formed at the surface of a wide range of polymers ͓polystyrene ͑PS͒, poly͑␣-methylstyrene͒, poly͑4-methylstyrene͒, PMMA, poly͑hydroxyadamantyl acrylate͒, and poly͑hydroxyadaman-tyl methacrylate͔͒ with a thickness of a few nanometers.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma–material interactions were explored in this study using an ICP system (Figure a). Such a reactor has been thoroughly described elsewhere . Briefly, the plasma was induced in the vacuum chamber by powering a planar, water‐cooled brass coil, located on top of a quartz window, through an L‐type matching network with a power supply at a frequency of 13.56 MHz.…”
Section: Experimental Details and Modelingmentioning
confidence: 99%